A review of phosphodiesterase type 5 inhibitors - N. Schellack; A. Agoro (South African Family Practice, 2014)
Currently, three phosphodiesterase type 5 (PDE5) inhibitors are available for clinical use in South Africa; sildenafil, vardenafil and tadalafil. The PDE inhibitors are used in males to treat erectile dysfunction. However, sildenafil is also registered for use in the treatment of pulmonary hypertension. Newer studies are investigating the use of these drugs for other conditions, including hypertension, ischaemia or reperfusion injury, myocardial infarction, cardiac hypertrophy, heart failure and other peripheral circulatory conditions, e.g. Raynaud’s disease. The article provides a broad overview of the mechanism of action, indications, pharmacokinetics and side-effects of these agents.